The Colonial Foundations of Malaysia's Terrorist Rehabilitation Program - Khor, Laura (Malaysian Journal of International Relations, 2013)
Malaysia's Terrorist Rehabilitation and Disengagement programs have shown positive results in detainee responses. Disengagement and de-radicalization are necessary elements in Malaysia's successful and comprehensive counter-terrorism strategies and policies. Malaysia's Terrorist Rehabilitation program employs academics, psychologists, policy makers, police, intelligence personnel, and religious leaders who have continually shaped this successful security program and anchored its' underlying disengagement security philosophy. The Malaysian Rehabilitation program's security philosophy and strategic framework have a unique history traced to the Malayan Emergency.